Sensitive to Proton Rhizotoxicity1 Regulates Salt and Drought Tolerance of Arabidopsis thaliana through Transcriptional Regulation of CIPK23. (26th May 2019) - Sadhukhan, Ayan; Enomoto, Takuo; Kobayashi, Yuriko; Watanabe, Toshihiro; Iuchi, Satoshi; Kobayashi, Masatomo; Sahoo, Lingaraj; Yamamoto, Yoshiharu Y; Koyama, Hiroyuki
Abstract: The transcription factor sensitive to proton rhizotoxicity 1 (STOP1) regulates multiple stress tolerances. In this study, we confirmed its involvement in NaCl and drought tolerance. The root growth of the T-DNA insertion mutant of STOP1 ( stop1 ) was sensitive to NaCl-containing solidified MS media. Transcriptome analysis of stop1 under NaCl stress revealed that STOP1 regulates several genes related to salt tolerance, including CIPK23 . Among all available homozygous T-DNA insertion mutants of the genes suppressed in stop1, only cipk23 showed a NaCl-sensitive root growth phenotype comparable to stop1 . The CIPK23 promoter had a functional STOP1-binding site, suggesting a strong CIPK23 suppression led to NaCl sensitivity of stop1 . This possibility was supported by in planta complementation of CIPK23 in the stop1 background, which rescued the short root phenotype under NaCl. Both stop1 and cipk23 exhibited a drought tolerant phenotype and increased abscisic acid-regulated stomatal closure, while the complementation of CIPK23 in stop1 reversed these traits. Our findings uncover additional pleiotropic roles of STOP1 mediated by CIPK23, which regulates various ion transporters including those regulating K + -homeostasis, which may induce a trade-off between drought tolerance and other traits.